2012
DOI: 10.4103/1319-3767.96445
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the mechanism of hepatic fibrosis and potential therapeutic approaches

Abstract: Hepatic fibrosis (HF) is a progressive condition with serious clinical complications arising from abnormal proliferation and amassing of tough fibrous scar tissue. This defiance of collagen fibers becomes fatal due to ultimate failure of liver functions. Participation of various cell types, interlinked cellular events, and large number of mediator molecules make the fibrotic process enormously complex and dynamic. However, with better appreciation of underlying cellular and molecular mechanisms of fibrosis, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 85 publications
0
64
0
3
Order By: Relevance
“…Excessive synthesis of ECM components leads to increased expression of α-SMA as well as changes in the expression of L-type voltage-operated Ca 2+ channels, which are known to mediate Ca 2+ influx and regulate cellular contraction (Gasull et al, 2001;Ahmad and Ahmad, 2012). In our study, HSCs co-cultured with HBx-expressing liver cells showed increased mRNA and protein expression of α-SMA compared to those cells co-cultured with live cells without expressing HBx.…”
Section: Effects Of Hbx On Hscsmentioning
confidence: 46%
See 1 more Smart Citation
“…Excessive synthesis of ECM components leads to increased expression of α-SMA as well as changes in the expression of L-type voltage-operated Ca 2+ channels, which are known to mediate Ca 2+ influx and regulate cellular contraction (Gasull et al, 2001;Ahmad and Ahmad, 2012). In our study, HSCs co-cultured with HBx-expressing liver cells showed increased mRNA and protein expression of α-SMA compared to those cells co-cultured with live cells without expressing HBx.…”
Section: Effects Of Hbx On Hscsmentioning
confidence: 46%
“…When HSCs are activated, excessive ECM products, particularly Col I, are produced and secreted (Pinzani and Marra, 2001;Ahmad and Ahmad, 2012). Thus, increased expression of Col I is an indicator of HSC activation.…”
Section: Effects Of Hbx On Hscsmentioning
confidence: 99%
“…58,59,226 These site-specific interventions have had their anti-fibrotic effects demonstrated in cell cultures, animal models, or preliminary human experiences and none has been integrated into a management algorithm. 60 Autoimmune hepatitis already has an effective therapy with drugs that have primary immunosuppressive and anti-inflammatory actions and secondary anti-fibrotic effects.…”
Section: Feasible Anti-fibrotic Interventions In Autoimmune Hepatitismentioning
confidence: 99%
“…157,166,193,263 Individualised modifications in conventional treatment may be beneficial, 16 and promising anti-fibrotic therapies that can supplement treatment must be evaluated and incorporated if validated. 58,59,226 Patients who are able to resolve all laboratory and histological manifestations of their disease within 6-12 months of conventional therapy have a low frequency of progressive hepatic fibrosis.…”
Section: Management Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation